The Role of Health Policy in Addressing the Hazards of Smoking: A Case Study of Law No. 36 of 2009 and Scientific Research Perspectives - Setiadin, Setiadin; Suradika, Agus; Samudra, Azhari Aziz; Murod, Ma'mun; Satispi, Evi; Ristiawati, Tia; Saefudin, Arif (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study was conducted to review the extent of the views of researchers in reviewing the implementation of Law No. 36 of 2009 concerning Health, especially related to the dangers of smoking through various fields of science and analysis of various problem focuses. The objectives of this study include analyzing the scope of the most discussed issues in scientific articles related to the implementation of Health Law No. 36 of 2009 on the dangers of smoking. The method used in this research is a literature study with a qualitative approach, using the literature study method and secondary data from the review of 35 scientific articles that have been published before August 2023. This research uses the PRISMA (Preferred Reporting Items for Systematic Review) systematic review method, which includes identification, screening, inclusion, and eligibility, and is then analyzed based on article findings. The results of the study showed that, of the many scientific articles on research that have been published, five problem areas were found to be the most widely discussed, namely: (1) the dangers of exposure to cigarette smoke, (2) smoke-free areas, (3) behavior in social relationships, (4) prevention efforts, and (5) smoking cessation efforts. These five focus issues have added to the discussions regarding the implementation of Law No. 36/2009 on Health related to smoking. This research provides insight into various aspects of health policy implementation related to the dangers of smoking. It emphasizes the need for further evaluation and action to improve the effectiveness of this policy.